2020
DOI: 10.3390/nu12092781
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Rich Flours from Quinoa and Buckwheat Favourably Affect the Growth Parameters, Intestinal Microbial Activity and Plasma Lipid Profile of Rats

Abstract: In recent years, dietary products with quinoa and buckwheat have attracted attention mostly due to the high nutritive value of their protein fraction. However, their dietary effect on intestinal microbiota activity and related systemic responses are still poorly understood. Therefore, a 2 week study of twenty-eight growing male Wistar rats was conducted to investigate the effects of quinoa (QU) and buckwheat (BK) protein-rich flours on the growth parameters, intestinal microbial activity, plasma lipid profile,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Fotschki et al. (2020) found that the body weight of rats fed with diets containing quinoa protein‐rich flour was lower than that of the control group.…”
Section: Physiological Effects Of Consuming Quinoamentioning
confidence: 99%
See 2 more Smart Citations
“…Fotschki et al. (2020) found that the body weight of rats fed with diets containing quinoa protein‐rich flour was lower than that of the control group.…”
Section: Physiological Effects Of Consuming Quinoamentioning
confidence: 99%
“…In vivo and human studies found that quinoa had mixed effects on weight gain. Studies have reported a significant decrease in body weight gain (BWG) associated with quinoa consumption in high‐cholesterol‐diet‐induced rats (Alghamdi, 2018; Halaby et al., 2017), nicotine‐induced rats (Ali, 2019), high‐sugar‐diet‐induced rats (de Oliveira Lopes et al., 2019; Mohamed et al., 2019), CCl 4 ‐induced rats (Al‐Qabba et al., 2020), healthy rats (Fotschki et al., 2020), and healthy humans (Pourshahidi et al., 2020). In contrast, in some studies, no significant change in body weight was observed in the healthy and obese rats supplemented with quinoa diet (Garcia‐Mazcorro et al., 2016; Matsuo, 2005; Noratto et al., 2019), and the same for the tested postmenopausal women (Carvalho et al., 2015), healthy adults (Farinazzi‐Machado et al., 2012), and overweight adults (Li et al., 2018; Navarro‐Perez et al., 2017).…”
Section: Physiological Effects Of Consuming Quinoamentioning
confidence: 99%
See 1 more Smart Citation
“…The final cytotoxic effects arise from not only the levels of bioactive substances, but also as a function of the synergistic actions among these. Thus, buckwheat protein-rich by-products are a good source of bioactive substances [ 25 , 26 , 27 , 28 , 29 ]. However, in-vitro antiproliferative effects on cancer cells do not always predict health-promoting effects, as the impacts must also be studied and confirmed in vivo.…”
Section: Quality Of Buckwheat Protein Compared To Soybean and Cerementioning
confidence: 99%
“…However, in-vitro antiproliferative effects on cancer cells do not always predict health-promoting effects, as the impacts must also be studied and confirmed in vivo. Some literature data [ 26 ] have stressed the need for a complex evaluation of the biological activities of buckwheat metabolites on intestinal health. Consumption of buckwheat protein extracts has been shown to slow mammary carcinogenesis in rats, which was connected with muscle hypertrophy and reduced hepatic triglyceride concentrations [ 30 , 31 , 32 , 33 ].…”
Section: Quality Of Buckwheat Protein Compared To Soybean and Cerementioning
confidence: 99%